PRAKTEK INTEGRASI VERTIKAL DAN DISKRIMINASI GRAB INDONESIA DAN PT TEKNOLOGI PENGANGKUTAN INDONESIA (PT. TPI) - Hendri Oktavianto (2021)
In business competition law, there are various prohibitions that are regulated in it, including vertical integration, and each of which is regulated in Article 14 and Article 19 letter d of Law No. 5 of 1999. The purpose of this study is to determine how the practice of vertical integration and legalization occurs, and the legal consequences of unfair business competition. The methods used are the legal approach (statute approach), the conceptual approach (conceptual approach), and the case approach (case approach). Grab Indonesia has a market of 70%, besides Grab Indonesia and PT. TPI is an affiliated company that results in facilitating practices in determining policies and strategies. Discrimination by Grab Indonesia as the applicator gives privileges to PT. TPI. From this case, it can be ignored that vertical integration and practice, are things that are prohibited in the law, which if violated has legal consequences.